Ekspolrasi Tingkat Pengetahuan dan Perilaku Body Shaming Mahasiswa di Kota Purwokerto - Yustria Puji Astuti; Wahyu Ekowati; Lita Heni Kusumawardani (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2022)
nd self-assessment that can arise due to dissatisfaction with what is owned by the individual. These behaviours can make individuals susceptible to body dysmorphic disorder. Objective: This study aims to explore the body shaming that exists among students in Purwokerto. Methods: This descriptive quantitative study used a cross-sectional approach. 1,165 students covering the number of all majors were then taken as many as 148 students with the inclusion criteria of active medical students, willing to follow until the end of the study, the exclusion criteria of students who could not complete the research until the end of data collection. The instrument in this study is a closed-ended questionnaire and uses the Guttman scale for its assessment with the categories of Good: 8-10, Enough: 6-7, Less: 0-5. Data were analyzed univariately and presented in the form of a frequency distribution. Results: The level of knowledge of students about body shaming is 89.9% and is included in the good category, while students' body-shaming behaviour is included in the medium category, namely 76.4%. The results of this study indicate that respondents who have a good level of knowledge can also perform body-shaming behaviour even though it is in the moderate category. Conclusion: The level of knowledge does not guarantee that individuals do not engage in body shaming behaviour. This behaviour can be avoided if the individual understands that it is not a good thing to do.